Weakly Supervised Character Detection for License Plate Recognition - Zeni , Luis F. A.; Jung, Claudio R. (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais da XXXIII Conference on Graphics, Patterns and Images, 2020)
Automatic Licence Plate Recognition (ALPR) is an essential task in the context of intelligent transportation systems. In a typical ALPR pipeline, the last stage receives as input a cropped license plate region and outputs the string with the plate characters. This paper presents a Weakly Supervised Character Detection (WSCD) approach that requires only string-level annotations (as in generic text recognition methods) but is able to detect characters individually (as in detection-based methods, which require character-level annotations). The proposed method is evaluated in five distinct datasets and present very competitive results against other state-of-the-art methods.